Study of Using R290 Refrigerant Replacement in a Heat Pump Application - Gratiela, Tarlea; George, Mardare; Ana, Tarlea (CLIMA 2022 conference, 2022)
The study represents a new approach in the research of the advantages obtained by the water-to-water heat pumps. This original system can use a renewable energy resource, respectively groundwater, rivers or sea water and can achieve both the heating and cooling requirements of a location. The study represents also a research in the field of energy efficiency and environmental optimization of heat pumps by changing the refrigerant R407C to R290. For testing, an open circuit water-to-water heat pump was used, with capillary evaporators in an original spiral shape able to avoid clogging, by continuous self-washing effect. The simulations showed that the heat pump ensures a reduction of the electricity consumption and Total Equivalent warming Impact by up to 50% compared to an ordinary air conditioning system.